The Effect of a 10-Week Physical Activity Programme on Fundamental Movement Skills in 3-4-Year-Old Children within Early Childhood Education Centres - Ajmol Ali; Claire McLachlan; Owen Mugridge; Tara McLaughlin; Cathryn Conlon; Linda Clarke (MDPI AG, 2021)
The objective of this study was to examine the effect of a 10-week physical activity (PA) programme, in early childhood education (ECE) settings, on 3 and 4-year-old children's fundamental movement skills (FMS). A further aim was to examine FMS three-months post-intervention. The PA instructors delivered one 45 min session/week over 10 weeks, to 3- and 4-year-old children (n = 46), across four ECE centres. These sessions involved participation from ECE teachers. Children in the control group (CON; n = 20) received no PA classes and completed pre- and post-intervention assessments only. Locomotor (e.g., running/hopping) and object-control (e.g., kicking/throwing) skills were assessed using the Test for Gross Motor Development-2 (TGMD-2), before and after the intervention and, for the intervention group (EXP), at 3 months. Locomotor and object-control skills significantly improved in the EXP group, with typically no change in the CON group. The EXP group's locomotor and object-control skills were maintained at 3 months. The 10-week PA intervention successfully improved 3- and 4-year-old children's FMS.